ANALISIS PENGUNGKAPAN SUSTAINABILITY REPORTS BERDASARKAN GRI STANDARDS PADA PERUSAHAAN ENERGI - Athaya Artanti Hanafi; Candratika Widayati Lestari; Erlinda Maretnaningsih Suwarno; Luthifa Salsabilla Arifin (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to evaluate the level of compliance of sustainability report disclosures based on the Global Reporting Initiative (GRI) Standards in four energy sector companies in Indonesia, namely PT Bukit Asam (PTBA) Tbk, PT Aneka Tambang (ANTM) Tbk, PT Timah (TINS) Tbk, and PT Alamtri Resources Indonesia (ADRO) Tbk for the period 2022-2024 using a qualitative descriptive approach method with content analysis of each company's sustainability report and comparing disclosures on indicators of universal standards and specific GRI standards. The results showed that all companies have achieved full compliance with GRI universal standards in the last two years (2023 and 2024), especially PTBA, ANTM, and TINS consistently maintain complete disclosure (100%) on GRI 100: Universal Standard for three consecutive years since 2022. Likewise, TINS managed to achieve 100% full disclosure for GRI specific standards 200, 300, 400 and ranked first for the 2023-2024 period compared to the other 3 companies. However, there are variations in disclosure on the economic, environmental and social specific standards between 4 companies. These findings confirm a commitment to transparency in the energy sector, but there is a need to improve the quality of reporting, particularly on social and environmental aspects to align with international standards.